Frail patients having vascular surgery during the early COVID‐19 pandemic experienced high rates of adverse perioperative events and amputation. Issue 9 (8th June 2022) - ,; Aitken, Sarah J.; Allard, Bernard; Altaf, Nishath; Atkinson, Noel; Aziz, Omar; Battersby, Ruth; Benson, Ruth; Chambers, Jennifer L.; Charlton, Gabriella; Coleman, Chloe; Dawson, Joseph A.; et al.
Abstract: Background: Frailty predicts adverse perioperative outcomes and increased mortality in patients having vascular surgery. Frailty assessment is a potential tool to inform resource allocation, and shared decision‐making about vascular surgery in the resource constrained COVID‐19 pandemic environment. This cohort study describes the prevalence of frailty in patients having vascular surgery and the association between frailty, mortality and perioperative outcomes. Methods: The COVID‐19 Vascular Service in Australia (COVER‐AU) prospective cohort study evaluates 30‐day and six‐month outcomes for consecutive patients having vascular surgery in 11 Australian vascular units, March–July 2020. The primary outcome was mortality, with secondary outcomes procedure‐related outcomes and hospital utilization. Frailty was assessed using the nine‐point visual Clinical Frailty Score, scores of 5 or more considered frail. Results: Of the 917 patients enrolled, 203 were frail (22.1%). The 30 day and 6 month mortality was 2.0% ( n  = 20) and 5.9% ( n  = 35) respectively with no significant difference between frail and non‐frail patients (OR 1.68, 95%CI 0.79–3.54). However, frail patients stayed longer in hospital, had more perioperative complications, and were more likely to be readmitted or have a reoperation when compared to non‐frail patients. At 6 months, frail patients had twice the odds of major amputation compared to non‐frail patients, after adjustment (OR 2.01; 95% CI 1.17–3.78), driven by a high rate of amputation during the period of reduced surgical activity. Conclusion: Our findings highlight that older, frail patients, experience potentially preventable adverse outcomes and there is a need for targeted interventions to optimize care, especially in times of healthcare stress. Abstract : This multicentre cohort study demonstrated that pre‐operative frailty was associated with adverse perioperative outcomes and increased major amputation but not mortality during the early COVID‐19 pandemic. This outcome disparity highlights the importance of targeted interventions to optimise the care of older, frail patients, especially in times of healthcare stress.